Institutional Control of Violence: Imperial Peace and Local Wars on the Slavonian Border in the Second Half of the 16th Century - Štefanec, Nataša (2013)
First, the paper questions was there a 'small war' on the Slavonian Border in the 16th century and how Habsburg military commanders, regular army and local noble landlords affected (largely Christian) population on the Ottoman side of the Border? Second, the paper analyzes institutional mechanisms of discovering and investigating localized peace-breaks on the border. Third, it identifies existing procedures aimed at sanctioning unsolicited violence and preserving peace among Empires. Fourth, it presents the development of formal, institutional mechanisms of violence control that increasingly enabled emerging state institutions to prevent various types of cross-border interaction of local population.
Projekt MZOS
ENG